Chapter 1: Introduction and Getting Ready for Hearing Aid Test Box Measures - Palmer, Catherine; Zitelli, Lori (Seminars in Hearing, 2024)
In this chapter you will be introduced to the hearing aid test box equipment and work through how to prepare the equipment so that it is ready to provide the testing you will use to evaluate, fit, and troubleshoot hearing aids and other amplifiers. At the end of this chapter, you will be familiar with terminology associated with hearing aid test box measures and the leveling required with the reference microphone and coupler microphone to ensure that your measurements are accurate and can be interpreted.
Keywords: hearing aid test box; calibration; leveling; coupler; coupler microphone